Performance materials with variations of tractor drive wheel fin angle and low-cost manufacturing analysis - saraswati, Sherly octavia; Purnomo, Endra Dwi; Aziz, Amiruddin; Nandar, Cuk Supriyadi Ali; Utomo, Setyo Margo; Marsalyna, Marsalyna; Nugroho, Fandy Septian; Amelia, Lia; Mubarak, Achmad Ridho; Hotma, Lambert (Jurnal Polimesin, 2024)
Nowadays, the demand for workers in the agriculture industry has decreased and there is a need for rising mechanization in the agriculture process. The agriculture process that requires mechanization is cultivating. The rice cultivator has to be as light as possible, so requires a lighter material but is also strong enough. The correlation between the rice transplanter tool and the wheels is closely related to soil conditions. The selection of wheel materials is considered based on the characteristics of the planting area. In addition, another influence variable is the angle of the fin in the rice transplanter wheel. Material of rice transplanter wheel has been established, these are 1023 carbon steel sheet, AISI 1020 steel cold rolled, AISI 316 stainless steel. The angle of the fin was varied, these are 30, 35, and 40, this fin will give an effect on the traction result of rice transplanter wheel movement. The combination of lightweight material and the appropriate fin angle of the rice transplanter wheel has the best traction result. As a result of this research, the suitable material for the rice transplanter wheel was carbon steel and the fin’s angle was 30. This research involved a comparison and analysis of material strength under various fin angles. The evaluation of stress criteria was conducted using design values to determine the most reliable final product design. The paper contributes by illustrating how to represent the final decision on the combination of design and materials, incorporating a cost index assessment.